A taxonomic revision of Mallotus Lour. section Mallotus (Muell. Arg.) Thin (Euphorbiaceae) in Vietnam - Thanh, Nguyen Thi Kim; Luu, Dinh Thi; Moi, La Dinh (Academia Journal of Biology, 2012)
Mallotus Lour. is a genus of shrubs, trees and climbers, with c. 150 species. The genus occurs mainly in (sub) tropical Asia, Australia and the Pacific, with only a few species in tropical Africa and Madagascar. Section Mallotus is one of six sections of genus Mallotus in Vietnam. A revision of Mallotus section Mallotus in Vietnam is given. There are seven species of this section occur in Vietnam: M. paniculatus, M. japonicus, M. apelta, M. metcalfianus, M. mollissimus, M. barbatus, M. macrostachyus. A new identification key to the species is provied. In this paper, 2 new varieties of M. paniculatus: Mallotus paniculatus var. paniculatus, Mallotus paniculatus var. formosamus, 3 new varieties of M. barbatus: Mallotus barbatus var. barbatus, Mallotus barbatus var. croizatianus, Mallotus barbatus var. pedicellaris and 2 new varieties of M. apelta: Mallotus apelta var. apelta, Mallotus apelta var. kwangsiensis are all described with the distribution and key to identify the varieties.